Magyar–szovjet kapcsolatok a szovjet kormány 1956. október 30-i nyilatkozata fényében - Baráth, Magdolna (Acta Scientiarum Socialium, 2016)
The Hungarian–Soviet Relations in Light of the Soviet Government’s Declaration of October 30, 1956. The Hungarian revolution in October 1956 was a watershed in the relationship of the two countries. This article focuses on the question of what kind of changes in the bilateral relationship were considered to be necessary by the Soviet and Hungarian parties, and to what extent these considerations were compatible with each other. The author reviews those measures that were destined for organizing the relations on the new basis (the arrangement of the legal status of the Soviet troops in Hungary, the question of Soviet advisers) and draws the readers’ attention to problems that remained unsolved between two countries.